Carotid intima–media thickness and endothelial function in adolescents exposed to alcohol consumption and cigarette smoking in utero: a mediation analysis - Tammy Hartel; Aamer Sandoo; André Oelofse; Juléy De Smidt (BMC Cardiovascular Disorders)
Abstract Background Previous studies have shown the effects of teratogen exposure in utero on the vascular system, but its direct and indirect effects are still questionable. Therefore, this study explored the effects of potential mediators of teratogen exposure on carotid intima–media thickness (cIMT) and flow-mediated dilation (FMD). Methods This study was conducted between January 2022 and August 2024 in Cape Town, South Africa, and included 307 adolescents (aged 10–14) and their mothers. Anthropometry data, lipid profiles, systolic (SBP) and diastolic blood pressure (DBP), physical activity and maternal health behaviours were obtained. Vascular measurements (left and right cIMT and brachial artery FMD) were obtained via ultrasound, which included analysing the peak artery diameter separately. Statistical analyses were performed via SPSS® version 29, and mediation analyses were conducted via PROCESS Macros. Results The cohort included a control group (n = 105), tobacco-exposed individuals (n = 115), dual-exposed individuals (tobacco and alcohol) (n = 73), and alcohol-exposed individuals (n = 14). A significant positive correlation was observed between alcohol exposure duration and LcIMT (rho = 0.531, p < 0.05), and a strong negative correlation was observed with peak diameter (rho=-0.788, p < 0.001), with a very strong correlation in males (r=-0.894, p < 0.05). The duration of alcohol exposure significantly affected LcIMT (p = 0.0468) after adjusting for body mass index (BMI), SBP and DBP. However, brachial artery (BA) peak diameter was not significantly associated with the duration of alcohol consumption during pregnancy after the adjustment for age, SBP or BA baseline diameter. Conclusion Increased BMI and SBP may contribute to a reduced peak diameter in adolescents exposed to alcohol, potentially indicating lower FMD in adulthood. Further studies should elucidate the biological mechanisms involved through long-term prospective studies.